Photocurrent enhancement in dye-sensitized photovoltaic devices with titania–graphene composite electrodes - Durantini, Javier Esteban (2012)
Photovoltaic performance of dye-sensitized solar cell (DSC) devices based on a new titania–graphene paste has been investigated using Impedance Spectroscopy (IS) technique. The results provide key information about device performance, clarifying that photocurrent increment is not related to lower charge transfer resistance, neither with a downshift of the Fermi level of the graphene titania semiconductor. The DSC devices constructed using titania–graphene paste and graphene thin films reach higher photocurrent and therefore higher efficiency than devices made with a commercial paste due to extra photocurrent generation, because the titania–graphene paste presents higher light harvesting in the visible region of the solar spectra combined with large scatter effect than the commercial titania paste.